Gravitational Higgs mechanism in neutron star interiors - Coates, Andrew; Horbatsch, Michael W.; Sotiriou, Thomas P. (American Physical Society, 2017)
We suggest that nonminimally coupled scalar fields can lead to modifications of the microphysics in the interiors of relativistic stars. As a concrete example, we consider the generation of a non-zero photon mass in such high-density environments. This is achieved by means of a light gravitational scalar, and the scalarization phase transition in scalar-tensor theories of gravitation. Two distinct models are presented, and phenomenological implications are briefly discussed.